Fruit-and-berry mash fermentation rate research - Poberezhets, Victor; Babich, Irina; Poberezhets, Ivan (My University, 2013)
Based on the Delle’s theory of preserving effect of sugar-alcohol solutions, obtained differential equation of mash fermentation. Decision of differential equation determines the alcohol content during fermentation and the rate of mash fermentation. Theoretical results are confirmed experimentally during fermentation of fruit-and-berry mash.
Keywords: mash fermentation; sugar-alcohol solution; fruit and berry jam; затор плодово-ягідний; бродіння затору; цукрово-спиртовий розчин; кафедра біотехнології продуктів бродіння і виноробства